Precision manufacture of spherical and aspheric surfaces on plastics, glass, silicon and germanium - Venkatesh, Vasisht, C. (2003)
This paper discusses the manufacture of aspheric and spherical surfaces in industries as well as in the universities with which the author is associated. Surfaces on plastics are produced by replicating them on glass moulds which, in turn, are replicated using ceramic moulds (for rotationally non-symmetrical lenses) or (for rotationally symmetrical lenses) ground on appropriate aspheric generators. The ceramic mould surfaces are generated on CNC milling machines. Rotationally symmetrical glass lenses were generated on both 4-axis and 5-axis CNC machining centres using both metal-bonded as well as resinoid-bonded cup grinding wheels. The same techniques were used for making lenses out of thermal imaging materials (silicon and germanium) where attempts to get semi-ductile mode of grinding were highly successful. The manufacture of spherical silicon lenses in industry is highlighted especially with respect to non-ductile regime grinding that increases polishing time. Results of surface texture and profile accuracy analyses using the Form Talysurf instrument are presented together with SEM pictures of the surfaces.